Open data kit (ODK) in crop farming: mobile data collection for seed yam tracking in Ibadan, Nigeria. Issue 5 (3rd September 2019) - Ouma, Turry; Kavoo, Agnes; Wainaina, Cornelius; Ogunya, Busayo; Karanja, Margaret; Kumar, P. Lava; Shah, Trushar
ABSTRACT: The purpose of this paper is to illustrate the importance of applying open-source technologies for mobile-based data collection for real-time tracking of seed yam ( Dioscorea rotundata and Dioscorea alata ) production. In the past, seed yam data in Nigeria have been predominantly collected using field notebooks, which were subsequently entered into a Microsoft Excel spreadsheet or Access database for analysis and reposition. Relevant areas of weakness within the current data systems include time delay in providing feedback and non-availability of data upon demand. As a result, this has hampered direct tracking of seeds at various stages of crop production and management. The study provided data collectors with a pre-installed yam seed tracking app for use on an Android device for data collection and management. The system architecture is based on the Open Data Kit (ODK) framework and a custom design based on requirements and lessons learned from literature. The ODK (Aggregate) made data easily accessible in minimum time possible from the point of data collection. The yam seed tracking application was developed as a result, which was field tested. The results indicated that this method improved efficiency, speed, and convenience in data collection and visualization, showing that this type of system can be used in crop management and research. The ODK was helpful to farmers in making their management decisions and ultimately boosting crop productivity. Stakeholders were able to visualize trends in yam production, which helps with marketing decisions.